The server: A media history from the present to the Baroque - Krajewski, Markus; Iurascu, Ilinca (Yale University Press, 2018)
Though classic servants like the butler or the governess have largely vanished, the Internet is filled with servers: web, ftp, mail, and others perform their daily drudgery, going about their business noiselessly and unnoticed. Why then are current-day digital drudges called servers? Markus Krajewski explores this question by going from the present back to the Baroque to study historical aspects of service through various perspectives, be it the servants’ relationship to architecture or their function in literary or scientific contexts. At the intersection of media studies, cultural history, and literature, this work recounts the gradual transition of agency from human to nonhuman actors to show how the concept of the digital server stems from the classic role of the servant.
CRIS-Team Scopus Importer:2023-03-21